2011
DOI: 10.1590/s0037-86822011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Could leprosy reaction episodes be exacerbated by oral infections?

Abstract: Introduction: This study evaluated whether leprosy reactions could be associated with oral infection. Methods: Leprosy patients (n = 38) with (group I) and without (group II) oral infections were selected. Reactions were identified from the clinical and histopathological features associated with serum C-reactive protein (CRP) and10kDa interferon-gamma-induced protein (IP-10) levels, determined before and after elimination of the foci of infection. Results: group I presented more reactions than group II did, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 9 publications
1
27
0
2
Order By: Relevance
“…Risk factors for development of LR include borderline form of disease, initiation of multidrug therapy, high bacillary load, stress and coinfections (Shegal & Sharma 1998, Balagon et al 2010, Motta et al 2011.…”
Section: Not Donementioning
confidence: 99%
“…Risk factors for development of LR include borderline form of disease, initiation of multidrug therapy, high bacillary load, stress and coinfections (Shegal & Sharma 1998, Balagon et al 2010, Motta et al 2011.…”
Section: Not Donementioning
confidence: 99%
“…Oral infections have also been suggested as risk factors for the occurrence of leprosy reactions, as indicated by an observed reduction in the rates of reactions after the establishment of dental treatment ( Motta et al 2011 ). After treatment, an elevated titre of circulating anti-phenolic glycolipid-1 (anti-PGL-1) IgM antibodies has been identified as a relevant marker for a reaction; seropositivity at MDT discharge corresponded to a 10-fold higher probability for the development of a reaction compared with that in patients with negative results ( Brito et al 2011 ).…”
mentioning
confidence: 99%
“…It has been observed that PBMCs present different levels of proliferation index of cytokines when they are stimulated in vitro with Mycobacterium leprae extracts [21][22][23] . On the other hand, we observed that the leprosy reactional episodes are frequent in patients presenting oral infections 14,15 and other coinfections 24 . Therefore, this study attempted to clarify whether chronic oral infections could influence the intracellular production of cytokines in leprosy patients, and to verify the relationship with the development of reactional episodes.…”
Section: A B C D Discussionmentioning
confidence: 72%
“…The coexistence of oral chronic infections with leprosy can modulate the inflammatory reaction by elevation of the intracellular inflammatory markers expression, probably stimulating a spill-over of these inflammatory products into the peripheral circulation where they can act as inducers of an inflammatory reaction, exacerbating the insidious chronic evolution of leprosy and, consequently, acting like an inducer, stimulatory or maintaining factor in leprosy reactions 14,15,24 . In addition, the presence of these chronic infections can influence the production of intracellular cytokines, and can reflect the fact that most of the leprosy patients with coinfection (Group I) presented reactional episodes, corroborating the hypothesis of a synergistic action of the two kinds of inflammatory reaction on the course of leprosy.…”
Section: A B C D Discussionmentioning
confidence: 99%
See 1 more Smart Citation